2018
DOI: 10.1177/0887403418806564
|View full text |Cite
|
Sign up to set email alerts
|

Educator Sexual Misconduct: A Statutory Analysis

Abstract: Educator sexual misconduct is a problem that has gained increased attention because of the high-profile cases reported by the news media. Yet, the diversity in state law regarding this offense remains somewhat unexplored. In this article, we compare and evaluate state statutory provisions regarding educator sexual misconduct; our focus is on what constitutes educator sexual misconduct, and what penalties are provided for offenders. As such, we explore the differences and similarities in statutory provisions ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Throughout this manuscript we use the terms teacher sexual misconduct and sexual misconduct by teachers to describe our phenomenon of study, which is the sexual contact that took place between a fictional teacher and student in our vignette study. This term is consistent with other research (see Frketic & Easteal, 2010;Fromuth et al, 2016;Knoll, 2010, Michaelis, 1996 and is sometimes used interchangeably with the term educator sexual misconduct (Abboud et al, 2020;Robert & Thompson, 2019;Shakeshaft, 2004). In the literature, sexual misconduct by teachers may involve a range of behaviors toward students with varying levels of coercion and/or violence (Frketic & Easteal, 2010).…”
Section: Terminologysupporting
confidence: 83%
See 1 more Smart Citation
“…Throughout this manuscript we use the terms teacher sexual misconduct and sexual misconduct by teachers to describe our phenomenon of study, which is the sexual contact that took place between a fictional teacher and student in our vignette study. This term is consistent with other research (see Frketic & Easteal, 2010;Fromuth et al, 2016;Knoll, 2010, Michaelis, 1996 and is sometimes used interchangeably with the term educator sexual misconduct (Abboud et al, 2020;Robert & Thompson, 2019;Shakeshaft, 2004). In the literature, sexual misconduct by teachers may involve a range of behaviors toward students with varying levels of coercion and/or violence (Frketic & Easteal, 2010).…”
Section: Terminologysupporting
confidence: 83%
“…201.540), any private or public-school employees over the age of 21 are prohibited from engaging in sexual conduct with students 17 years of age and younger, despite 16 otherwise being the legal age of consent. Similar laws exist in many states across the country with the goal of protecting minors from sexual abuse at school (see Abboud et al, 2020 for an overview of U.S. statutes). Though data on teacher sexual misconduct prevalence is limited given varying definitions and inconsistent reporting systems, one study found that nearly 10% of all students in grades 8 to 11 have been victims of sexual misconduct by an educator, defined in this study as ranging from sexual harassment to abuse (Shakeshaft, 2004).…”
mentioning
confidence: 99%
“…Despite frequent media attention to incidents of sexual abuse by a teacher, the exact magnitude of the problem remains largely unknown (Abboud et al, 2020). Estimating the prevalence of the problem has proven to be difficult given discrepant reporting standards (e.g., districts or communities having different definitions or reporting standards for what constitutes abuse), incomplete or inaccessible documentation (e.g., those who experience and perpetrate the abuse are not easily identifiable by researchers), and difficulties in collating information given the differences in reporting systems and standards by states and school districts.…”
Section: Prevalencementioning
confidence: 99%
“…While these rates of alleged sexual abuse were significantly higher than those obtained from the last Office of Civil Rights data collection in 2015-2016 (53% increase for sexual assault and 99% increase for rape/attempted rape), they likely represent an underestimate of the true prevalence of the problem as the data are based only upon official reports. Further, Abboud et al (2020) suggests that educator sexual misconduct may be greatly underestimated in general due to measurement difficulties and an abundance of cases that go unreported or unrecorded.…”
Section: Prevalencementioning
confidence: 99%
“…Academic employee moral misconduct is potential harm to the institution irrespective of the benefits to be gained by such employee (Ayodele, Yao, & Haron, 2018). To this end, organizations are keen on mechanisms that will enhance the moral behavior of their employees to mitigate the undesirable effects of employee misconduct (Abboud, Wu, Pedneault, Stohr, & Hemmens, 2017). Employee moral behavior is the ability of the employee to form the right opinion about acceptable principles of right or wrong behavior based on applicable ethical standards (He, Zhu, & Zheng, 2014).…”
Section: Introductionmentioning
confidence: 99%